Performance Studies of Electric and Combustion Engines: The Case of a Conventional Vehicle in Benin - ZOGBOCHI, Victor (My University, 2024)
Electric agility provides reduced cost of movement, as well as savings in energy and harmful pollutant transmission. In this study, we focus briefly on the types of motors used for electric traction, through an examination of various factors: speed, efficiency, cost and reliability. Our study also highlights the type of motor used in the hybridization of conventional vehicles in Benin, as well as a comparative study between the internal combustion engines operating in Benin and the associated electric motor in the same speed range. The sole aim is to highlight the positive impact of hybridizing conventional vehicles in Benin, without affecting existing technology. From the analysis of motor types, we note that this heading has been the subject of literature review articles by several authors, so it emerges that brushless DC and permanent magnet motors are reputed choices for electric mobility. The comparative survey carried out between the internal combustion engine and the electric motor at globalized regulatory speeds (driving cycle) shows that performance characteristics are similar, albeit with some differences, enabling us to opine on the need for hybridization to progressively facilitate independence from the internal combustion engine.
Keywords: Surveys; Costs; Torque; Accuracy; Bibliographies; Internal combustion engines; Permanent magnet motors; Combustion; Reliability; Electric motors